Makna Kurikulum: Dari Materi Belajar Ke Perencanaan Pembelajaran - Muhammad, Ismail (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2015)
The term â€œcurriculumâ€ is derived from the Latin word â€œcurriculaeâ€ which etomologically means â€œdistance in runningâ€. Terminologically, curriculum has been interpreted in terms of contextual changes in education, they are; course of study, educative experience and plan for learning